Evaluation of reaction to plant density of sunflower hybrids by regression and Kang’s stability analysis - Szabó, András (Acta Agraria Debreceniensis, 2008)
The world production area and the total production of sunflower has significantly been growing. The harvested yield was 23.4 and 21.1 million ha in 2005 and 2001, respectively. The total sunflower seed production has also unexpectedly increased.Although sunflower is produced on lower quality soils in Hungary, in 2005 the average harvested yield was 2.43 t ha-1, which was the highest in the world. Sunflower is a typical commercial plant and fits well in the crop structure. Since in terms of acreage the most significant crops are corn and cereals, the partial monoculture cultivation cannot be avoided. Sunflower production is a way to eliminate this problem, therefore it has an important role both in cultivation and ecological points of view.Accordingly, sunflower has an important role in reducing the monoculture cultivation of some plants, as well as increasing biodiversity. Sunflower well adapts to Hungary’s climatic conditions and its production is easily practicable in our country.The reaction of sunflower hybrids on crop density change is different. Some hybrids are more some are less sensitive to this parameter. In different crop years, the crop density optimums of the different genotypes are also different. In Hungary, the yield and quality is primarily determined by fungal infections, while viruses and bacteria are less important.The research was conducted at the Látókép farm and Regional Research Institute of the University of Debrecen, Centre of Agricultural Sciences. The research institute is situated by Road 33,15 km from Debrecen in the Hajdúság. The duration of the experiment was seven years, 10 hybrids were examined in each year.Two hybrids used every year, Aréna/PR and Alexandra/PR hybrids were tested by Kang’s stability analysis. We found that Alexandra/PR was most balanced at every levels of crop density. Both hybrids performed most stable yield at 65000 ha-1 crop density level and less balanced at 35000 ha-1 crop density level. As a result of improved environmental conditions, the yield increase of Aréna/PR was higher than that of Alexandra/PR.Our regression analysis found that the maximum yield of Lympil, Louidor, Hysun 321, PR63A82 and PR64A63 hybrids were harvested at 47000-60000 plant ha-1 crop density level. The statistical analysis showed that the highest yield was harvested from Lympil and Hysun 321. As regards the crop yield, the most stable hybrids were Louidor and Lympil. The optimum crop density interval of Rigasol/PR and Larisol (58000 plant ha-1) was wider than that of Diabolo (46000 plant ha-1). The maximum yield of Larisol was higher at the optimal crop density level. As regards yield, Diabol was the most stable hybrid.The statistical analysis on the stability of the yield of Alexandra/PR and Aréna/PR showed that Aréna/PR is more stable, and its optimal crop density level is lower than that of Alexandra/PR.